Synopsis of Epipleoneura (Zygoptera, Coenagrionidae, “Protoneuridae”), with emphasis on its Brazilian species - Pessacq, Pablo (Zootaxa, 2014)
A revision of the known species of Epipleoneura is presented. Material of all Brazilian species was examined. Two new species are described: E. ottoi (Holotype: Brazil, Goiás State, São Bartolomeu river) and E. susanae (Holotype: Brazil, Mato Grosso State, São Lorenzo river), and the male of E. humeralis and the female of E. kaxuriana are described for the first time. With the exception of E. protostictoides, diagnoses, morphological characterizations, and illustrations of all species including known females are presented. The genital ligula of 25 species is described or redescribed. Morphological intraspecific variation is presented for E. machadoi, E. metallica, and E. venezuelensis.